2011
DOI: 10.1021/jp2032737
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and Irreversible Light-Induced p-Doping of P3HT by Oxygen Studied by Photoelectron Spectroscopy (XPS/UPS)

Abstract: The influence of oxygen and light on the energy level alignment of poly(3-hexylthiophene) thin films (∼100 nm) is investigated quantitatively using X-ray and ultraviolet photoelectron spectroscopy (XPS/UPS) in order to probe energetic shifts and the element distribution in the film. Upon simultaneous exposure to oxygen and light a reversible shift of the occupied states of about 0.3 eV is observed together with the presence of reversibly and irreversibly bound oxygen species. Whereas the reversibly bound speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
75
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 24 publications
13
75
0
1
Order By: Relevance
“…New bands at about 1520-1560 cm −1 and 1656-1680 cm −1 (CvC asymmetric stretching vibrations in the polythiophene chain) appeared (Fig. 44,45 Moreover, as presented by Hintz et al 46 polythiophene also undergoes spontaneous oxidation in the presence of oxygen and light. All these changes fully confirm the formation of conjugated polythiophene chains and are very well described in the literature for different polythiophene-based polymers.…”
Section: Template Oxidative Polymerization With Feclmentioning
confidence: 52%
“…New bands at about 1520-1560 cm −1 and 1656-1680 cm −1 (CvC asymmetric stretching vibrations in the polythiophene chain) appeared (Fig. 44,45 Moreover, as presented by Hintz et al 46 polythiophene also undergoes spontaneous oxidation in the presence of oxygen and light. All these changes fully confirm the formation of conjugated polythiophene chains and are very well described in the literature for different polythiophene-based polymers.…”
Section: Template Oxidative Polymerization With Feclmentioning
confidence: 52%
“…Finally, the presence of unwanted oxygen, either in its diatomic or radical state, has been shown to form trap states in the semiconductor density of states of the blend [55][56][57] , thus altering device performance. It has been suggested that this could additionally electronically dope the blend material 12,14,16,58 . Evidently there are uncertainties around the actual cause of the electronic doping, however we have shown here that this is a significant effect that must be considered and should be the subject of further study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, polymer:fullerene solar cells are not intentionally doped like their inorganic counterparts or like many small molecule solar cells 11 and therefore rely on selective contacts and the difference in work function between electrodes for efficient charge collection. However, several studies have found evidence for unintentional doping [12][13][14][15][16][17][18][19] and discussed the consequences for device behaviour 6,[20][21][22][23][24][25][26][27][28][29][30] . Whilst the origin of this doping is unclear 15 , its effects on photovoltaic performance can be substantial; however many recent analyses of device performance neglect doping 8,[31][32][33] despite the fact that the influence of doping and the electric field on charge carrier collection is well known for a long time 34 and wellstudied for instance in the field of quantum dot photovoltaics 35,36 .…”
mentioning
confidence: 99%
“…6,[12][13][14][15][16][17][18][19][20][21][22] Specifically, exposure of these systems to air leads to the creation of shallow 13,23,24 and deep 6,13,22,[25][26][27] carrier traps. Even though the formation of shallow traps may lead to p-type doping of the organic semiconductor, 23,[28][29][30][31] overall, the creation of trap sites is detrimental for the performance of the material as it limits carrier mobilities. 28 Experimental studies 17,[32][33][34][35] have suggested that oxygen may react with P3HT polymer chains and form a number of different products.…”
Section: Introductionmentioning
confidence: 99%